Implementation and Analysis of a Synchronisation Protocol for Fair Exchange with Strong Fairness and Privacy - Quixabeira, Dhileane; Teles-Borges, Mailson; Roos-Frantz, Fabricia; Frantz, Rafael Z.; Sawicki, Sandro; Molina-Jimenez, Carlos; Crowcroft, Jon (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2025: Anais do XXV Simpósio Brasileiro de Cibersegurança, 2025)
Strong fairness ensures that in fair exchange protocols, items are either exchanged or remain with their original owners. Privacy, another key property, prevents the leakage of sensitive information. Achieving both simultaneously is challenging. Existing protocols that ensure strong fairness, such as those in online payments, fail to guarantee privacy due to reliance on monolithic trusted third parties. These entities perform critical actions that expose data. We propose replacing them with a split trusted third party model, composed of two trusted execution environments (one per participant) and a public bulletin board used solely for synchronisation. Our analysis and implementation show that this approach preserves strong fairness, strong timeliness and privacy.